Uji Pembakaran Biobriket Tongkol Jagung dan Sekam Padi Menggunakan Perekat Sagu - Suratin, Dedi Mardeni; Barata, La Ode Ahmad; Aminur, Aminur (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
The main source of energy for humans is Human Resources which comes from carbon fossils. This energy has been deficient so it needs to be energy differentified. Biobriquettes are charcoal bars using soft materials that are processed into hard charcoal materials. The purpose of this study was to determine the composition of a good mixture (not easily destroyed) based on the compressive strength of the Corn Cob and Rice Husk biobrikets and to determine the flame temperature of the Corn Cob biobriket and Rice Husk. The method carried out in this study is the analysis of the flame temperature and compressive strength contained in the briquettes. The analysis carried out in this study was carried out with 5 variations in composition, namely ( corn cobs 25% : rice husks 75% : sago 15%, corn cobs 75% : rice husks 25% : sago 15%, corn cobs 50% : rice husks 50% : sago 15%, corn cobs 100% : rice husks 0% : sago 15%, and corn cobs 0% : rice husks 100% : sago 15%). From the results that have been obtained, briquettes that have good quality are found in corn cobs 25%: Rice husks 75%: sago 15% with a temperature value of 500 °C and a maximum load strength value of 159,060 with a compressive strength value of 1.0404624 N / mm2.Keywords: Corn cobs, rice husks, and flame temperature